The amplifying influence of increased ocean stratification on a future year without a summer. Issue 1 (December 2017) - Fasullo, J.; Tomas, R.; Stevenson, S.; Otto-Bliesner, B.; Brady, E.; Wahl, E.
Abstract In 1816, the coldest summer of the past two centuries was observed over northeastern North America and western Europe. This so-called Year Without a Summer (YWAS) has been widely attributed to the 1815 eruption of Indonesia's Mt. Tambora and was concurrent with agricultural failures and famines worldwide. To understand the potential impacts of a similar future eruption, a thorough physical understanding of the YWAS is crucial. Climate model simulations of both the 1815 Tambora eruption and a hypothetical analogous future eruption are examined, the latter occurring in 2085 assuming a business-as-usual climate scenario. Here, we show that the 1815 eruption drove strong responses in both the ocean and cryosphere that were fundamental to driving the YWAS. Through modulation of ocean stratification and near-surface winds, global warming contributes to an amplified surface climate response. Limitations in using major volcanic eruptions as a constraint on cloud feedbacks are also found. The 1815 eruption of Mt. Tambora caused one of the strongest climate perturbations in the modern record; the 1816 year without a summer. Here, the authors show that climate change, through its impact on ocean stratification, strengthens the surface response to such an eruption.